Hippotherapy: therapeutic and educational interventions with people with disabilities and with Autistic Spectrum Disorder (Research, Society and Development, 2021)
The objective is to report the therapeutic and educational interventions of horse-assisted therapy in people with disabilities and with Autistic Spectrum Disorder (ASD), during participation in the extension project in Hippotherapy at the University of Passo Fundo (UPF). This is a descriptive, qualitative study, of the experience report type. It was decided to list in topics the explanation of the experience, namely: a) the team that develops the project; b) location and schedule of activities; c) how much the participating patients; d) regarding the interventions performed during therapy; e) regarding the interventions carried out during the pandemic. We will report the experiences lived in the hippotherapy sessions encompassing basic and structural characteristics of the project and the interventions and actions carried out during it. It is concluded that the experience with hippotherapy provides the creation of a link between the practitioners and nature, provides physical, psychological, moral, social and spiritual results for the practitioners and the team that implements it. It also promotes differentiated training, developing interdisciplinary teamwork and thus providing holistic assistance.